Angular emission properties of a layer of rare-earth based nanophosphors embedded in one-dimensional photonic crystal coatings - Sánchez Sobrado, O. (2011)
The angular properties of light emitted from rare-earth based nanophosphors embedded in optical resonators built in one-dimensional photonic crystal coatings are herein investigated. Strong directional dependence of the photoluminescence spectra is found. Abrupt angular variations of the enhancement caused by the photonic structure and the extraction power are observed, in good agreement with calculated polar emission patterns. Our results conﬁrm that the optical cavity favors the extraction of different wavelengths at different angles and that integration of nanophosphors within photonic crystals provides control over the directional emission properties that could be put into practice in phosphorescent displays.